Correlative in vivo 2 photon and focused ion beam scanning electron microscopy of cortical neurons - Maco, Bohumil; Holtmaat, Anthony; Cantoni, Marco; Kreshuk, Anna; Straehle, Christoph-Nikolas; Hamprecht, Fred; Knott, Graham W. (PLOS ONE, 2013)
Correlating in vivo imaging of neurons and their synaptic connections with electron microscopy combines dynamic and ultrastructural information. Here we describe a semi-automated technique whereby volumes of brain tissue containing axons and dendrites, previously studied in vivo, are subsequently imaged in three dimensions with focused ion beam scanning electron microcopy. These neurites are then identified and reconstructed automatically from the image series using the latest segmentation algorithms. The fast and reliable imaging and reconstruction technique avoids any specific labeling to identify the features of interest in the electron microscope, and optimises their preservation and staining for 3D analysis.